Influence of maternal human immunodeficiency virus (HIV) and antiretroviral (ARV) drugs on neonate neurometabolism. - Masina, Nosipho (Department of Human Biology, 2024)
The human immunodeficiency virus (HIV) can be vertically transmitted from a woman living with HIV to her child during pregnancy, childbirth, and breastfeeding. Antiretroviral therapy (ART) prevents vertical transmission of HIV by providing prophylaxis to the fetus or infant and lowering the mother's viral load (VL). Due to the prevention of vertical HIV transmission, there is a decrease in infants acquiring HIV vertically. Correspondingly, there is an increasing population of HIV-exposed and uninfected (HEU) infants and children, with the current global estimate of HEU infants and children at around 15 million. While results have been inconsistent, some studies show that HEU children have an increased risk of morbidity and mortality, as well as neurodevelopmental delays across language, motor and cognitive domains, when compared to their HIV-unexposed and uninfected (HUU) counterparts. Several factors have been associated with the higher morbidity and mortality rates exhibited by HEU children. These factors include perinatal and postnatal (during breastfeeding) exposure to maternal HIV and ART, a pro-inflammatory state in the mother, and a compromised maternal immune system. This study aimed to see if the metabolic brain abnormalities seen in older HEU children could be detected in neonates. Based on previous results, we hypothesize lower ratios of glutamate (Glu) to total creatine (creatine plus phosphocholine) (Glu/Cr+PCr), N-acetyl-aspartate (NAA) to Cr+PCr (NAA/Cr+PCr), and choline-containing compounds phosphocholine plus glycerophosphocholine (GPC+PCh) to Cr+PCr (GPC+PCh/Cr+PCr) in the basal ganglia (BG) of HEU neonates compared to HUU neonates, as seen previously for absolute concentrations of these metabolites in 9-year-old HEU children. Furthermore, we hypothesized lower Glu/Cr+PCr and NAA/Cr+PCr ratios in the midfrontal gray matter (MFGM) of HEU neonates compared to HUU neonates, as previously observed for absolute concentrations of Glu and NAA in 11-year-old HEU children. Using proton magnetic resonance spectroscopy (MRS), metabolite/Cr+PCr ratios were measured in the BG (83 HEU neonates and 45 HUU neonates) and MFGM (65 HEU neonates and 31 HUU neonates) of neonates at a mean gestational age (GA) equivalent of 41.56 weeks (range 39-45 weeks). Linear regression models were used to compare HIV and ART exposure group differences in metabolite/Cr+PCr ratios in HEU neonates and HUU neonates, as well as HEU neonates who have been exposed to ART since conception (pre-conception) and HEU neonates who have been exposed to ART after 5 weeks of GA to HUU neonates. NAA/Cr+PCr, GPC+PCh/Cr+PCr, Glu/Cr+PCr, and myo-inositol (Ins)/Cr+PCr were the metabolite/Cr+PCr ratios measured.